Impact of coal composition and pore structure on gas adsorption: a study based on a synchrotron radiation facility. Issue 1 (11th November 2019) - Sun, Yingfeng; Zhao, Yixin; Yuan, Liang
Abstract: A better knowledge about the impact of coal composition and pore structure on gas adsorption is of great significance for coalbed methane exploration and uneconomic coalbed CO2 storage. Coal is a porous medium with complex organic components, and most pores in coal are nanopores that have a complex geometrical morphology. As a result, it is significantly necessary to investigate the impact of coal composition and pore structure on gas adsorption based on coal 3D nanopore structure. Synchrotron radiation nano‐computed tomography (CT) was applied to acquire 3D coal nanopore structure and synchrotron radiation small‐angle X‐ray scattering (SAXS) was used to obtain the pore surface fractal dimension. The coal with higher pore surface fractal dimension presents higher Langmuir volume. Based on the 3D nanopore structure acquired by synchrotron radiation nano‐CT, gas adsorption capacity was characterized by the adsorbed gas amount on unit pore surface area. It was found that gas adsorption capacity depends on the coal composition. There is a negative correlation between gas adsorption capacity and ash content and oxygen‐containing groups, and a positive correlation between gas adsorption capacity and vitrinite contents. Hysteresis between desorption and adsorption isotherms is dependent upon the ratio of throat number to pore number, and the hysteresis becomes more significant when the ratio is larger. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.